Tourism management an introduction - Inkson, Clare (SAGE, 2018)
This text offers a concise introduction to all the core topics of tourism management. Covering both key theory and practice, it introduces general management issues across the whole tourism sector, focusing particularly on the challenges of managing tourism in the 21st century.